The Evolving Standard of Care for Autoimmune Neuropsychiatric Illness - He, Cynthia; Morris, Nathaniel; McNiel, Dale; Binder, Renee (Journal of the American Academy of Psychiatry and the Law Online, 2024)
In recent decades, there has been increasing biomedical and public understanding of the role of autoimmunity in neuropsychiatric illness. Popular media have highlighted patients with psychiatric illnesses who were eventually diagnosed with autoimmune neuropsychiatric illnesses such as anti– N-methyl-D-aspartate receptor encephalitis. Coverage of these cases has often drawn attention to the effects of misdiagnosis or delayed diagnosis of such diseases in psychiatric patients. Autoimmune encephalitis can have varied presentations and often involves evaluation and management from multiple medical specialties. As a result, there remains considerable uncertainty regarding how courts might gauge the legal standard of care with regard to psychiatric workup of new-onset psychiatric symptoms, and the degree to which autoimmune encephalitis must be considered. In this article we provide a brief overview of autoimmune encephalitis and autoimmune psychosis, including current diagnostic approaches to these conditions. We review case law regarding the standard of care for psychiatric disorders caused by general medical conditions. Finally, we provide a medicolegal perspective on the responsibilities of psychiatrists and other mental health professionals in the evaluation of possible autoimmune encephalitis.